2006
DOI: 10.1007/s10265-006-0011-x
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphisms for elucidating the genetic structure of the heavy-metal hyperaccumulating trait in Thlaspi caerulescens and their cross-genera amplification in Brassicaceae

Abstract: Genetic polymorphism was investigated in Thlaspi caerulescens J. & C. Presl at 15 gene regions, of which seven have been identified to putatively play a role in heavy-metal tolerance or hyperaccumulation. Single nucleotide and length polymorphisms were assessed at four cleaved amplified polymorphic sequences (CAPS) and 11 simple sequence repeat (microsatellite) loci, respectively. The utility of these loci for genetic studies in T. caerulescens was measured among seven natural populations (135 individuals). Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 39 publications
0
21
3
Order By: Relevance
“…In particular, the higher density of markers in the QTL intervals provided by this work has drastically reduced the length of the QTL two-LOD support intervals from 24, 4 and 13 cM ) to 5, 3 and 12 cM for Zntol-1, Zntol-2 and Zntol-3, respectively. Moreover, most of these primers can probably be used to amplify other Brassicaceae species, as shown by Basic and Besnard (2006), who reported that, using primers anchored on gene coding sequences, 70% of cross-species PCR amplification between species representative of Brassicaceae was successful. Consequently, the primers designed in this study can be further used as a source of transferable gene markers for comparative mapping analyses among species in the Brassicaceae family.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In particular, the higher density of markers in the QTL intervals provided by this work has drastically reduced the length of the QTL two-LOD support intervals from 24, 4 and 13 cM ) to 5, 3 and 12 cM for Zntol-1, Zntol-2 and Zntol-3, respectively. Moreover, most of these primers can probably be used to amplify other Brassicaceae species, as shown by Basic and Besnard (2006), who reported that, using primers anchored on gene coding sequences, 70% of cross-species PCR amplification between species representative of Brassicaceae was successful. Consequently, the primers designed in this study can be further used as a source of transferable gene markers for comparative mapping analyses among species in the Brassicaceae family.…”
Section: Discussionmentioning
confidence: 95%
“…Most of the primers amplifying these newly defined markers were designed in exons (maximizing cross-species amplification of the markers), to amplify fragments displaying a size between 600 and 850 base pairs (bp) and to scan for polymorphism between species, within at least one intron. The sequences of the primers Tc-up3, Tc-up2, Ah-IRT2 were designed in Thlaspi caerulescens by Basic and Besnard (2006). To obtain labelled PCR products detectable on the automated genotyper Li-Cor 4200 (Li-Cor-ScienceTec), the forward and reverse primer contained a 5′-tail of 19 bp (forward primer) or 20 bp (reverse primer) homologous to the universal consensus M13 primer sequence, followed by the locus-specific sequence (Oetting et al 1995).…”
Section: Genetic Marker Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The last cycle was followed by a 10-min extension at 72°C. Electrophoresis procedures were used as described by Basic and Besnard (2006).…”
Section: Plastid Dna Characterizationmentioning
confidence: 99%
“…Digestion of the PCR fragments was performed using the restriction enzyme TasI (Fermentas, St Leon-Rot, Germany) according to the manufacturer's recommendations. Electrophoresis procedures were used as described by Basic and Besnard (2006).…”
Section: Plastid Dna Characterizationmentioning
confidence: 99%